PASTORALISM IN MONGOLIA AS AN ESSENCE OF THE NOMADIC CIVILIZATION.: Z. BATJARGAL, B. ENKHJARGAL - Z. BATJARGAL, B. ENKHJARGAL (Acta Mongolica, 2012)
A simple superposition of reconstructed trends of climate parameters, particularly, the temperature trends at the global and regional scales and Mongolia's historical timeline could give an impression that certain commonly accepted perceptions about nomadic tribes could be revised. Most scholars concluded that Mongols and their ancestors had been migrating with war and attacks of their neighbors due to the worsening climate conditions. Nevertheless, a detailed analysis can provide a diverse evidence, which include opposing views.